If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + -9 = 9a Reorder the terms: -9 + 8a = 9a Solving -9 + 8a = 9a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9a' to each side of the equation. -9 + 8a + -9a = 9a + -9a Combine like terms: 8a + -9a = -1a -9 + -1a = 9a + -9a Combine like terms: 9a + -9a = 0 -9 + -1a = 0 Add '9' to each side of the equation. -9 + 9 + -1a = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1a = 0 + 9 -1a = 0 + 9 Combine like terms: 0 + 9 = 9 -1a = 9 Divide each side by '-1'. a = -9 Simplifying a = -9
| -14+5t-36=1-1 | | 2w+7=4w-1 | | -x^2+3x-18=0 | | 12x=(4x+40)*2 | | 4z=-5z-18 | | -18+5x=13+-12x-1 | | -(x+4)+4x=23 | | 81x^3-1=0 | | x+8-(x-1)=5(x+2) | | 3-2x=-11 | | -18+15x=17x | | x-21=25-3x | | 4x+40=(4x+40)*2 | | -2x-6-3=1 | | 2(6d+3)=18-3(16d-3d) | | -104=-6x-3x+4 | | 10a+5[a-3]=15 | | 3-x+3=5x | | 6-8x=7x-10+11 | | 14-3a+7a=94 | | 4q+4=-2q-8 | | -6(x-1)=14-2x | | 9x-27=9(11-x) | | 6-2x=-12 | | -2x+4(3x+5)=-60 | | 0.3x-0.4=2 | | 7p-5=69+8 | | 5(x+2)=(x+6) | | -8k+k=-14 | | x/4-x/3= | | .5x+5=17 | | 2(x+1)+4=16 |